Counseling across cultures - Pedersen, Paul, 1936-; Lonner, Walter J.; Draguns, Juris G., 1932-; Trimble, Joseph E.; Scharrón-del Río, María R. (SAGE, 2015)
* The book is edited by pioneers in the field who helped found the multicultural movement in the 1980s. * A useful five-part, 24-chapter format provides balanced coverage. * Broad coverage explores a wide range of topics, from spirituality in counseling across cultures to culturally appropriate counseling interventions with diverse client populations. * Critical Incidents (expanded cases) offer students the opportunity to analyze and think critically about a variety of cultural situations.- Resumé vydavatel
Keywords: multikulturní poradenství; psychologické poradenství; interkulturní psychologie; transkulturní psychoterapie; multicultural counseling; psychological counseling; cross-cultural psychology; transcultural psychotherapy; elektronické knihy; kolektivní monografie; electronic books; collective monographs